TOURISM DEVELOPMENT STRATEGY OF MAHORO ISLAND IN SITARO REGENCY, NORTH SULAWESI - Angelina T. Palandung; Maria Heny Pratiknjo; Very Yohanis Londa (Transpublika Publisher, 2025)
This study examines the potential for tourism development on Mahoro Island, located in the Siau Tagulandang Biaro (Sitaro) Regency of North Sulawesi. 3A approach which focuses on attractions, amenities, and accessibility is utilized. The research adopts a qualitative methodology and follows systematic data analysis procedures as outlined by Miles and Huberman, including data disaggregation, clear presentation of findings, and the formulation of conclusions. The findings indicate that Mahoro Island possesses remarkable natural attractions, including exquisite white sandy beaches and an abundance of marine life. However, there are notable challenges; the management of these attractions is currently inadequate. Additionally, the island's amenities, such as accommodations and various services, are in need of significant enhancement. Furthermore, access to and navigation around the island are impeded by limited transportation options and suboptimal port facilities. To address these challenges, it is imperative to improve the management of tourist sites, upgrade the available facilities, and enhance transportation alternatives. Furthermore, fostering collaboration among government entities, tourism businesses, and local communities is crucial for achieving sustainable tourism development in the region. By focusing on these three components, we aim to position Mahoro Island as a premier tourist destination and contribute to the growth of the local economy.